Eastern Vector of Russian State Policy Development for Ensuring Energy Security - Kapitonov, Ivan A.; Voloshin, Vladimir I.; Korolev, Vitaly G. (International Journal of Energy Economics and Policy, 2018)
This article is dedicated to the current problem of forming the Eastern vector of oil and gas policy within new energy policy and modern circumstances. The main goal of the work is to study the energy relations between Russia and the countries of the Asia-Pacific region, namely China. Using the analysis method, authors have highlighted the threats and possibilities of the influence of the current situation in the fuel and energy complex on Russia's energy security. Analysis of the existing situation on the global energy market has revealed that deepening and expansion of partnerships in economic and energy sphere with China are of interest to Russia as a Eurasian state. The basis for a partnership is a cooperation, based on China's demand for natural resources, while Russia will benefit from using effective innovation models of modernisation. Keywords: Asia-Pacific Region, Energy Sphere, Oil and Gas Policy, Raw Material Resource Potential, Energy Security, Energy Dialogue. JEL Classifications: P48, Q40.